2011
DOI: 10.1074/jbc.m111.265835
|View full text |Cite|
|
Sign up to set email alerts
|

Conserved, Disordered C Terminus of DnaK Enhances Cellular Survival upon Stress and DnaK in Vitro Chaperone Activity

Abstract: The 70-kDa heat shock proteins (Hsp70s) function as molecular chaperones through the allosteric coupling of their nucleotide-and substrate-binding domains, the structures of which are highly conserved. In contrast, the roles of the poorly structured, variable length C-terminal regions present on Hsp70s remain unclear. In many eukaryotic Hsp70s, the extreme C-terminal EEVD tetrapeptide sequence associates with co-chaperones via binding to tetratricopeptide repeat domains. It is not known whether this is the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 59 publications
4
79
0
Order By: Relevance
“…In this case, direct interactions between the lid and the substrate were observed, leading to even further extension of the conformational space available within the Hsp70s’ SBD. This direct lid-substrate interaction, as well as the recently described interaction between the unstructured C-terminus of Hsp70 chaperones and their substrates 64 , might aid in conformational remodeling of Hsp70 clients. The ATP-induced opening of the lid 51; 52 and the inherent dynamics observed for the lid 48; 57 might also have an impact on substrate conformations if lid-substrate interactions occur.…”
Section: The Atpase Cycle Of Bip In the Er Environmentmentioning
confidence: 79%
“…In this case, direct interactions between the lid and the substrate were observed, leading to even further extension of the conformational space available within the Hsp70s’ SBD. This direct lid-substrate interaction, as well as the recently described interaction between the unstructured C-terminus of Hsp70 chaperones and their substrates 64 , might aid in conformational remodeling of Hsp70 clients. The ATP-induced opening of the lid 51; 52 and the inherent dynamics observed for the lid 48; 57 might also have an impact on substrate conformations if lid-substrate interactions occur.…”
Section: The Atpase Cycle Of Bip In the Er Environmentmentioning
confidence: 79%
“…They showed that a relatively short truncation (35 residues) led to loss of viability under stringent conditions (absence of SecB) and loss of ability to efficiently refold denatured luciferase in vitro . 36 In addition, the C-terminus of E. coli DnaK became more ordered when DnaK bound to a protein model substrate (a stably unfolded staphylococcal nuclease mutant) but not when bound to a peptide. 36 Taken together these studies suggest that protein substrates may bind to the C-terminus of Hsp70s in addition to the canonical substrate-binding groove.…”
Section: The Basis Of Substrate Recognition By Hsp70smentioning
confidence: 99%
“…36 In addition, the C-terminus of E. coli DnaK became more ordered when DnaK bound to a protein model substrate (a stably unfolded staphylococcal nuclease mutant) but not when bound to a peptide. 36 Taken together these studies suggest that protein substrates may bind to the C-terminus of Hsp70s in addition to the canonical substrate-binding groove. This type of binding may serve multiple purposes–keeping the substrate more unfolded and also keeping the substrate in the local region of the chaperone even after ATP-mediated release, to facilitate rebinding if necessary.…”
Section: The Basis Of Substrate Recognition By Hsp70smentioning
confidence: 99%
“…The C terminus of Hsp70 is also disordered, but its exact role in chaperone activity remains controversial. Smock et al presented evidence that the C terminus of Hsp70 encodes a weak auxiliary peptide binding motif that is important for chaperone activity in vitro [43]. However, Aponte et al performed an in vivo selection for enhanced chaperone activity and found that truncation of 35 residues from the disordered C terminus of Hsp70 actually increased in vivo and in vitro chaperone activity [44].…”
Section: Molecular Chaperones: Prototypes Of Proteins With Multiple Bmentioning
confidence: 99%
“…However, Aponte et al performed an in vivo selection for enhanced chaperone activity and found that truncation of 35 residues from the disordered C terminus of Hsp70 actually increased in vivo and in vitro chaperone activity [44]. One explanation for these apparently conflicting results is that chaperones bind their own disordered regions and thus might treat themselves as substrates [43]. Disordered regions in chaperones like Hsp70 would thus be acting as covalently linked inhibitors.…”
Section: Molecular Chaperones: Prototypes Of Proteins With Multiple Bmentioning
confidence: 99%